Role of electrocardiography and echocardiography in prevention and predicting outcome of subjects at increased risk of heart failure. (29th August 2020) - Bello, Vitantonio Di; Carrubba, Salvatore La; Antonini-Canterin, Francesco; Salvo, Giovanni Di; Caso, Pio; Canna, Giovanni La; Erlicher, Andrea; Badano, Luigi; Romano, Maria Francesca; Zito, Concetta; Vriz, Olga; Conte, Lorenzo; et al.
Abstract: Background: Asymptomatic left ventricular dysfunction (ALVD) is relatively common in both community and high-risk populations. Early pharmacological intervention can improve clinical outcomes in subjects with this condition. Objectives: This multicentre study consists on electrocardiographic and echocardiographic examination of stage A and B heart failure (HF) asymptomatic subjects with one or more cardiovascular risk factors, to assess the prognostic value of cardiovascular risk factors per se, clinical history, and electrocardiographic and echocardiographic parameters in prediction of progression of HF and/or in development of cardiovascular primary or secondary events. Material and methods: A total of 2142 asymptomatic subjects (mean age 63 years, 1162 males) performed an electrocardiographic and echocardiographic examination. Electrocardiogram (ECG) pathological signs according to Minnesota code and left ventricular dysfunction both systolic and diastolic by echocardiography were evaluated. There were 2002 subjects who were followed up for 26 ± 11 months, observing their primary and secondary end points. Results: At follow up, the study population presented 111 primary end points (5.2%) and 441 secondary end points (20.6%). ECG criteria of LV hypertrophy and signs of ischaemia or previous myocardial infarction ( p < 0.0001) were highly significantly related to primary end points. Both ECG and echocardiography (systolic function) are able at Kaplan–Meier cumulative survival curves to predict primary end points ( p < 0.0001). Conclusions: Presence or absence of left ventricular systolic and /or diastolic dysfunction has an incremental value in comparison to cardiovascular risk factors, clinical history, and ECG findings to predict both the evolution towards a more severe HF stage (stage C) and also the occurrence of cardiovascular events.